The Effectiveness of Public-Private Partnerships in Addressing Residential Urban Development Challenges in Greater Cairo - Abdelmessih, Sara Nagy (AUC Knowledge Fountain, 2026)
This research explores the effectiveness of Public-Private Partnerships (PPPs) in tackling the residential urban development challenges facing Cairo today. In the past two decades, PPPs have emerged as a dominant mode of housing production, positioned as collaborative ventures between state agencies and private developers. They have become integral to the expansion of Greater Cairo, producing vast new urban extensions under the promise of mobilizing private capital, technical expertise, and delivery capacity. Yet, questions remain about whether these arrangements genuinely address Egypt’s most urgent housing needs, or whether they reproduce market-driven logics that leave large segments of the population excluded. The study engages this question through three interconnected layers of analysis. The first maps the landscape of stakeholders shaping the housing market in Egypt, revealing a complex web of public entities, private actors, and foreign-led financial institutions. The second examines four local PPP case studies that reflect different partnership structures and outcomes, each offering insights into the challenges of governance, financial structuring, and risk-sharing. The third introduces a comparative dimension through the Dutch case of Leidsche Rijn. Rather than serving as a blueprint, this case is used to illuminate how different governance cultures and planning traditions, coupled with the constant updated data accumulation on both the population and existing housing stock can open alternative ways of framing PPPs and their potential for more inclusive development. By situating these case studies within the wider context of Cairo’s urban challenges ranging from high vacancy rates to persistent affordability gaps; the research argues that PPPs in Egypt remain constrained by a narrow focus on land provision and revenue generation. Their current form does little to address the deeper structural misalignments between housing supply and actual demand. The findings highlight the need for a recalibrated PPP framework one that is based on informed planning, one that positions the public sector not only as a land allocator but as a genuine urban development actor capable of safeguarding social value, integrating citizen needs, and steering housing provision toward a more sustainable and equitable future.